Work and pay in the United States and Japan - Brown, Clair 1946-. (New York Oxford University Press, 1997)
In Work and Pay in the United States and Japan, authors Clair Brown, Yoshifumi Nakata, Michael Reich, and Lloyd Ulman provide an integrated and detailed analysis of the employment and wage systems in the United States and Japan. Drawing on data obtained from fieldwork in comparable establishments in these two countries, as well as from national sources, this work examines the relationship between company practices and national economic institutions. The authors address a number of key questions about employer-employee relations. How have major Japanese manufacturing companies been able to convert the assurance of "lifetime" employment security into a source of superior employee efficiency and adaptability, when job and income security have been feared as a source of "shirking" and wage inflation in the United States? How have higher economic and real wage growth rates been associated with greater equality in earned income distribution in Japan, when the incentive role of income inequality to worker effort and savings has been stressed in the United States? How could Japanese emphasis on employment security in the firm be reconciled with greater price stability and lower unemployment than in the United States? This work analyzes elements such as employee training and involvement programs, wage behavior as an incentive system and an alternate channel of savings, and synchronous wage determination (Shunto) at work in the Japanese economy that provide for such successes. The book also explores the costs that have been associated with these Japanese accomplishments, as well as who must bear them. In particular, it examines how the situation of Japanese women compares less favorably with that of American women in terms of opportunities for work, pay, and promotion; the higher hours of working time for men in Japan than in the United States; and the constraints on mobility for Japanese workers. It also poses the question of whether Japanese unions are weaker than their American counterparts or just more sensible and farsighted. Finally, this work examines the outlook for these distinctive Japanese institutions and practices in a period of slower growth and economic "maturity."
Keywords: Industrial management -- Japan; Industrial management -- United States; Labor -- Japan; Labor -- United States; Industrial relations -- Japan; Industrial relations -- United States; Employees -- Training of -- Japan; Employees -- Training of -- United States; Wage payment systems -- Japan; Wage payment systems -- United States; Labor productivity -- Japan; Labor productivity -- United States; Comparative management; Japan -- Economic conditions -- 1945-.; United States -- Economic conditions -- 1945-.